Substituent variation drives metal/monolayer/semiconductor junctions from strongly rectifying to ohmic behavior - Haj-Yahia, Abd-Elrazek (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.